Prosthodontic management of children with ectodermal dysplasia: A literature review - Abdulaziz. A. Alowairdhi (Saudi Dental Journal)
Introduction: Ectodermal dysplasia (ED) is a large group of heterogeneous heritable conditions characterized by congenital defects of two or more ectodermal structures and their appendages. The diagnosis of ED in early infancy period may be difficult in that sparse hair and absent teeth are normal findings at this stage of development. However, characteristic deformities of the skull including the square aspect of the forehead; frontal bossing; sunken cheeks; hyperpigmentation of the periorbital skin; prominent supraorbital ridges; saddle nose; and hypoplastic-appearing alaque nasi helps in diagnosing ED cases. In addition to its other symptoms, the dental characteristics of this syndrome include number anomalies such as anodontia or severe hypodontia (with or without a cleft lip and palate) that is associated with lack of alveolar ridge development and reduced vertical dimension. Clinically there are two major types of ED namely hidrotic and anhidrotic (hypohidrotic form). The hypohidrotic form is most common type with an incidence estimated to be 1–7 per 10,000 live births. The goals of dental treatment for individuals affected by the ED syndromes are to provide an age-appropriate dentition that optimizes function, facial development, speech and esthetics. Dental management of children with ectodermal dysplasia includes removable, fixed and implant prosthesis. Materials and Method: A computerized search of the literature was done by searching the web based databases PubMed, Up To Date and the University of Texas Health Science Center for Critically Appraised Topics (CATS) library for key words including: Ectodermal Dysplasia, Prosthodontic Management of Ectodermal Dysplasia, Oral Manifestations of Ectodermal Dysplasia and Fixed and Removable Prosthodontic Management of Ectodermal Dysplasia. Titles and abstracts of the studies were evaluated according to relevance after obtaining the full text articles. The search ended in January 2017. The inclusion criteria were: studies that evaluated different modalities of treatment of ectodermal dysplasia, studies that addressed the effects of ectodermal dysplasia on oral health, reviews that addressed the clinical consequences of ectodermal dysplasia, case reports and case series of ectodermal dysplasia. Exclusion criteria: studies that were directed or focused to other aspects of ectodermal dysplasia other than oral health. Results: These patients often need a multidisciplinary approach to treatment planning and dental treatment to regain esthetics and function of the stomatognathic system. Considering the age, different rehabilitation options can be considered, from classic conventional solutions such as complete denture, removable partial denture, overdentures and to the most up to date implant supported prosthetics. Conclusion: Recall every 6 months with possible relining, rebasing or making a new denture. Following growth completion and occlusion stabilization an implant retained removable or fixed denture can be used to replace the missing teeth permanently. Moreover, traditional removable denture can be an option for replacing the missing teeth. However, implants provide the best long term results and prognosis.